Loosely-packed dynamical structures with partially-melted surface being the key for thermophilic argonaute proteins achieving high DNA-cleavage activity. Issue 13 (29th June 2022) - Zheng, Lirong; Lu, Hui; Zan, Bing; Li, Song; Liu, Hao; Liu, Zhuo; Huang, Juan; Liu, Yongjia; Jiang, Fan; Liu, Qian; Feng, Yan; Hong, Liang
Abstract: Prokaryotic Argonaute proteins (p Ago s) widely participate in hosts to defend against the invasion of nucleic acids. Compared with the CRISPR-Cas system, which requires a specific motif on the target and can only use RNA as guide, p Ago s exhibit precise endonuclease activity on any arbitrary target sequence and can use both RNA and DNA as guide, thus rendering great potential for genome editing applications. Hitherto, most in-depth studies on the structure-function relationship of p Ago s were conducted on thermophilic ones, functioning at ∼60 to 100°C, whose structures were, however, determined experimentally at much lower temperatures (20–33°C). It remains unclear whether these low-temperature structures can represent the true conformations of the thermophilic p Ago s under their physiological conditions. The present work studied three p Ago s, PfAgo, TtAgo and CbAgo, whose physiological temperatures differ significantly (95, 75 and 37°C). By conducting thorough experimental and simulation studies, we found that thermophilic p Ago s ( PfAgo and TtAgo ) adopt a loosely-packed structure with a partially-melted surface at the physiological temperatures, largely different from the compact crystalline structures determined at moderate temperatures. In contrast, the mesophilic p Ago ( CbAgo ) assumes a compact crystalline structure at its optimal function temperature. Such a partially-disrupted structure endows thermophilic p Ago s with great flexibility both globally and locally at the catalytic sites, which is crucial for them to achieve high DNA-cleavage activity. To further prove this, we incubated thermophilic p Ago s with urea to purposely disrupt their structures, and the resulting cleavage activity was significantly enhanced below the physiological temperature, even at human body temperature. Further testing of many thermophilic Ago s present in various thermophilic prokaryotes demonstrated that their structures are generally disrupted under physiological conditions. Therefore, our findings suggest that the highly dynamical structure with a partially-melted surface, distinct from the low-temperature crystalline structure, could be a general strategy assumed by thermophilic p Ago s to achieve the high DNA-cleavage activity.